2015
DOI: 10.1007/s00784-015-1623-0
|View full text |Cite
|
Sign up to set email alerts
|

Are self-adhesive resin cements suitable as core build-up materials? Analyses of maximum load capability, margin integrity, and physical properties

Abstract: The investigated experimental self-adhesive resin cement cannot be recommended as a core build-up material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
7
0
7
Order By: Relevance
“…The use of pins will probably continue to decrease given the risks of placement and the advent of more durable adhesive bonding agents and composite resins (6,35,36). This in vitro research proved and concluded that the retentive shoulder design offers a conservative and safe approach in the prevention of early failures by enhancing and increasing the micro retention and resistance form of core builds-ups when restoring structurally compromised vital posterior teeth.…”
Section: Assessment Of Force Required To Remove Temporary Crownmentioning
confidence: 86%
“…The use of pins will probably continue to decrease given the risks of placement and the advent of more durable adhesive bonding agents and composite resins (6,35,36). This in vitro research proved and concluded that the retentive shoulder design offers a conservative and safe approach in the prevention of early failures by enhancing and increasing the micro retention and resistance form of core builds-ups when restoring structurally compromised vital posterior teeth.…”
Section: Assessment Of Force Required To Remove Temporary Crownmentioning
confidence: 86%
“…Rely X Unicem, 3M, Seefeld) [42]. Diese können jedoch nicht für die Herstellung des koronalen Aufbaus empfohlen werden [43]. Signifikant schlechtere mechanische Eigenschaften wie geringere Biegefestigkeit, höhere Wasseraufnahme, geringerer E-Modul, höhere Polymerisationsschrumpfung wurden für ein selbstkonditionierendes Adhäsivsystem im Vergleich zu Mehrschritt-Adhäsivsystemen mit separatem Primer (traditionell als Etch-and-Rinse-Adhäsivsystem bezeichnet) im humanen Dentin festgestellt.…”
Section: Wichtig: Haftverbundunclassified
“…Rely X Unicem, 3M, Seefeld) [43]. Diese können jedoch nicht für die Herstellung des koronalen Aufbaus empfohlen werden [44]. Signifikant schlechtere mechanische Eigenschaften wie geringere Biegefestigkeit, höhere Wasseraufnahme, geringerer E-Modul, höhere Polymerisationsschrumpfung wurden für ein selbstkonditionierendes Adhäsivsystem im Vergleich zu Mehrschritt-Adhäsivsystemen mit separatem Primer (traditionell als Etch-and-Rinse-Adhäsivsystem bezeichnet) im humanen Dentin festgestellt.…”
Section: Merkeunclassified